Assertive Behavior of Students Based on the Perspective of Parenting, Culture, and Self-Esteem: A Systematic Literature Review - Syahputra, Muhammad Evryan; Syukur, Yarmis; Wahid, Ahmad; Althafunnisa, Shannon Nurul; Sihombing, Sri Cahaya; Mukhtahari, Murtadha (Program Studi Bimbingan dan Konseling Islam, 2025)
Assertive behavior plays a fundamental role in an individual’s life. Good assertive behavior can have a positive impact on one’s life. Various factors can potentially determine different assertive behaviors in each individual, which then need to be analyzed. Therefore, it is very important to examine and analyze students’ assertive behavior from various perspectives. Based on this, this study was conducted with the aim of analyzing students’ assertive behavior from the perspectives of parenting, culture, and self-esteem. This study uses a systematic literature review method. This systematic literature review was conducted following the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) standards, where the stages in this review include identification, screening, suitability, and inclusion. Literature sources were collected through Scopus and Web of Science. The results of an in-depth systematic literature review then drew the conclusion that parenting, culture, and self-esteem are factors that can predict students’ assertive behavior. The researchers recommended various follow-up studies based on the results of this study. These include conducting research on other parenting patterns that have not been explored in this paper, to be linked to assertive behavior. Then, conducting research on assertive behavior by integrating it with the existing culture in Indonesia.